Design and implementation of passive impedance adapter to damp resonances between VSC‐HVDC and AC systems - Changyue Zou; Junjie Feng; Xiaobin Zhao; Yi Yuan; Ting Hou (IET Generation, Transmission & Distribution)
Abstract It has been known that resonances often occur when high‐voltage direct current (HVDC) systems are connected into the AC system via voltage‐source converters (VSCs). The resonances may lead to system failure and even damage primary equipment under some severe conditions. However, the existing damping methods are inadequate to ensure the system is always stable. To solve it, this article introduces the passive impedance adapter (PIA) in parallel with VSC to compensate the negative impedance of VSC‐HVDC system especially at mid‐ and high‐frequency ranges. A novel design and implementation method for the PIA is then proposed with the reduced volume and power loss to ensure the whole system impedance always positive. By this way, no resonance exists and the system is stable under any practical condition, such as the different cable lengths and impedances. Finally, a simulation platform is built to verify the effectiveness of the proposed PIA method in compensating the VSC‐HVDC impedance.